Disgenesia gonadal con fórmula cromosómica XO/XX/XXX - Güell González, Ricardo; Padrón Durán, Rubén S.; Egües Sánchez, Célida; Gómez de Molina, Concepción (Revista Cubana de Pediatría, 2023)
Presentación de caso